Gestaltningsfloran - Eriksson, Oskar (2009)
Contemporary plant design can be examined by how it relates to two extremes - Nature and Art. This idea is explained by Noel Kingsbury in the book The Dynamic Landscape where he places designers and their projects on a gradient (Kingsbury, 2004). Nature, one of the extremes can be represented by a dynamic, species-rich plant design with native species and with nature as the ideal. The other extreme - Art implies a more static view on plant design. Here, the designs consist of colourful flowers, exotic species and cultivars with double flowers. According to this perspective the human-controlled culture is the ideal. Traditionally when we describe the qualities of plants it's done through one of these perspectives - either through the horticultural, aestetic perspective or through the ecological, naturalistic perspective. For this thesis I have examined if it is possible to create a database that can store and handle species-specific information with perspectives from both sides. The goal has been to create a model for such a database and investigate how it can be designed. What should it contain and how are traits of species described? By studying existing systems and literature on the subject, I have experimented with such a system. I chose to work with a computer-based program as the media for the database. It lends flexibility and can easily store big quantities of data. The user is not dependent on the internet but it can still be used as a channel to exchange information. The main function has been leading the design work. How is it made possible to search for species through standardised criteria and how is information about the biotopes handled? Other important factors have been identified to guide the design work. The database should be user-friendly, inspiring, information-rich and flexible. To create an interface that is easy to navigate, the graphic design has been inspired by an old file-cabinet. Most of us have an idea how they work. The database is organised so that the species can be divided into 12 different profile-types. The information in the profiles is sorted under four different files: Taxonomy, Characteristics, Ecology and Management & Establishment. In the first file, Taxonomy, data about the name, family, functional group and classification of the plant is handled. In the Characteristics-file traits that are horticulturally associated are handled i.e. colour of the flower, colour of the leaves, scent etc. In the Ecology-file the natural habitat and the ecological range of the species are described. Here, the user can see under what circumstances a species can compete, its physiological optimum and its tolerance range. The strategy-balance and the distribution in Sweden are also described here. In the last file, the Management & Establishment-file, factors connected to caretaking are described. While the work has progressed the extent of this subject has become clear for me. The goal to create a system that works for all types of users was unrealistic. Different needs demand different solutions and the way the information is presented has to be adapted to the knowledge levels of the different users. Even if the database isn't ready to be programmed, the project has still brought me a lot of knowledge and hopefully my ideas can be developed and used in new contexts.